Crop reconversion as a result of the presence of huanglongbing in Colima, Mexico - Granados-Ramírez, Guadalupe Rebeca (2018)
The state of Colima is known as the main producer of lemon. In 2010 the presence of citrus greening or Huanglonbing (HLB), a disease affecting, was detected in this region and has since translated into multiplying losses. Up to this date, no cure for it is known and the low profitability of the production forces growers to withdraw their crops. Therefore, the productive reconversion modifies the production pattern by establishing alternate crops with a higher agronomic and social feasibility, as well as a better economic profitability. The main goal of this research was to quantify the changes in the crops and to assess the potential of introducing new ones. In order to monitor, identify and quantify such changes, satellite imagery analysis, building and analysis of agricultural databases, on site measurements and interviews were conducted. An increasing number of crops were substituted, close to 5,000 ha of citrus have been replaced, which amounts to a reduction of  84,721 tons in the production of Mexican lemon and a loss of $302, 636,729 MXN,  approximately. The area of emergent crops such as papaya and pineapple keeps increasing and has represented a higher income for producers.